2011
DOI: 10.1523/jneurosci.3280-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Phox2b-Expressing Neurons of the Parafacial Region Regulate Breathing Rate, Inspiration, and Expiration in Conscious Rats

Abstract: The retrotrapezoid nucleus contains Phox2b-expressing glutamatergic neurons (RTN-Phox2b neurons) that regulate breathing in a CO2-dependent manner. Here we use channelrhodopsin-based optogenetics to explore how these neurons control breathing in conscious and anesthetized adult rats. Respiratory entrainment (pacing) of breathing frequency (fR) was produced over 57% (anesthetized) and 28% (conscious) of the natural frequency range by burst activation of RTN-Phox2b neurons (3–8 × 0.5–20 ms pulses at 20 Hz). In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
156
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(183 citation statements)
references
References 49 publications
16
156
1
5
Order By: Relevance
“…ABD EMG activity was also potentiated during CO 2 stimulation, consistent with previous reports (Iizuka and Fregosi, 2007;Marina et al, 2010;Abbott et al, 2011).…”
Section: Chemosensitivity Under Urethane Anesthesiasupporting
confidence: 91%
See 1 more Smart Citation
“…ABD EMG activity was also potentiated during CO 2 stimulation, consistent with previous reports (Iizuka and Fregosi, 2007;Marina et al, 2010;Abbott et al, 2011).…”
Section: Chemosensitivity Under Urethane Anesthesiasupporting
confidence: 91%
“…Abdominal muscles are not generally active at rest but are frequently activated during quiet sleep in healthy humans, in patients with obstructive sleep apnea, and in snorers (Skatrud and Dempsey, 1985;Skatrud et al, 1988). In rats, abdominal expiratory-related activity is induced or potentiated by chemosensory stimulation (Iizuka and Fregosi, 2007;Marina et al, 2010;Abbott et al, 2011), exercise, and selective stimulation of the para-facial respiratory group (Pagliardini et al, 2011) [the proposed expiratory rhythm generator (Mellen et al, 2003;Janczewski and Feldman, 2006)]. Thus, it is possible that ABD EMG recruitment during REM-like periods was caused by increased respiratory drive.…”
Section: State-dependent Respiratory Muscle Modulation During Urethanmentioning
confidence: 99%
“…Indeed, studies in adult cat in vivo preparation (Bainton and Kirkwood 1979;Sears 1977) demonstrated that rhythmic discharges of expiratory bulbospinal units in the medulla were observed to change into a tonic firing pattern. Active expiration was induced effectively by unilateral optogenetic stimulation of the pFRG and a neighboring retrotrapezoid nucleus (Abbott et al 2011;Pagliardini et al 2011), but interactions between pFRGs on the stimulated and contralateral side were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de várias evidências mostrando o envolvimento do pFRG/RTN na inspiração, mais recentemente estudos têm procurado associar o pFRG/RTN também à atividade expiratória (ABBOTT et al, 2011;FELDMAN et al, 2011).…”
Section: Envolvimento Da Região Pfrg/rtn Na Expiraçãounclassified
“…A musculatura da laringe esta envolvida em diversas funções fisiológicas como o funcionamento adequado das cordas vocais, na regulação da abertura da glote, no controle da resistência das vias aéreas e em reflexos protetores das vias aéreas (HORNER, 2013 (TAKAKURA et al, 2006;, mas uma região integradora de respostas autônomas (MOREIRA et al, 2007a;TAKAKURA et al, 2011; TAKAKURA; MOREIRA, 2011) e respiratórias (ABBOTT et al, 2011(ABBOTT et al, , 2013MOREIRA et al, 2007b;presentes resultados).…”
Section: Envolvimento Da Região Pfrg/rtn Na Fase Pós-inspiratóriaunclassified